Preparation of activated carbon from oil palm empty fruit bunch for adsorption of phenol and hydrogen - Md. Arshad, Siti Hadjar (2013)
This study was carried out to investigate the potential of empty fruit bunch (EFB) based activated carbon (AC) as a phenol and hydrogen adsorbent. The precursor was prepared in laboratory tube furnace by carbonization in nitrogen flow followed by carbon dioxide activation at 900°C, 10°C/min under 15 minutes residence time and treatment with potassium hydroxide (KOH) solvent at different concentrations (i.e. 0.5M, 1.0M and 2.0M). The optimization study on carbonization parameters; temperature, heating rate, and residence time on the phenol removal was investigated by using response surface methodology (RSM) with box-benken design. The optimal process conditions obtained was; 500°C carbonization temperature, 10°C/min of heating rate, and 80 min of residence time; which given 7.57% of phenol removal. The best condition EFB fibre size was the one with greater than 2 mm mesh size; gave 73% of phenol removal. The kinetics of adsorption was well described by pseudo-second order model whilst the adsorption equilibrium was best represented by Langmuir isotherm model. Hydrogen adsorption study was analysed at ambient pressure by Accelerated Surface Area and Porosimetry analyzer (ASAP 2020) and at high pressure by high pressure volumetric analyzer (HPVA). The AC that was activated by physical and followed by impregnated with 2M KOH adsorbed a maximum hydrogen adsorption capacity value of 2.14 wt% at 19 bars and -196.15 °C. Regeneration study was carried out by sodium hydroxide (NaOH) treatment and the regeneration efficiency (RE) of the AC has been reduced to 42 % after the third treatment. The Breuner, Emmer and Teller (BET) study showed that the ACs produced have surface area between 489 to 687 m2/g. This study has identified EFB has a potential to be used as a precursor in the preparation of AC for phenol and hydrogen adsorbent.